Analysis of the nature and severity of injuries in patients with traumatic lesions of the brachial plexus - Strafun, Serhii; Lysak, Andrii (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
Brachial plexus lesions (BPL) is a severe, disabling pathology is mostly occur in young patients of working age. Often, BPL is combined with other injuries, which significantly aggravate the diagnosis, and therefore delay the start of treatment. Objective: to analyze the characteristics of injuries in patients with traumatic BPI, that has been surgically treated at our center. Methods: retrospective analysis of 237 patients was performed, study included only patients with traumatic brachial plexus injuries, that has been surgically treated at our center, from 2000 to 2019. All patients underwent a thorough anamnesis, orthopedic-neurological examination, radiography, ultrasound, CT, MRI, NCS, ENMG. Particular attention was paid to the etiology, anatomical localization of the lesion, and presence of associated lesions. Results: 84.4 % of patients with BPL had other injuries. In patients of the younger age group (up to 50 y. o.) among the causes of this injury prevailed motorcycle road-traffic accident with root lesions, while in patients after the age of 50 y. o. — fell with injury at the level of cords. Root avulsions are characterized by high energy trauma, while lesions of the brachial plexus cords result from low-energy trauma. Most characteristic of the preganglionic injuries of the brachial plexus were their combination with traumatic brain injury and chest injuries, while for the injury at the level of cords were humerus fractures. Retroclavicular injuries (injury at the devisions level) were characterized by both combination of closed traumatic brain injury and fractures of clavicle and humerus. Conclusions: Most common BPL occur in three critical zones: preganglionic — 36.3 %, subclavicular — 35.4 %, and retroclavicular — 20.3 %. Risk group of patients with BPL should include patients with polytrauma, patients who had injuries traffic accident, falling or significant upper extremity traction.